Cultural tensions as the catalyst of intergenerational trauma in The Joy Luck Club - Navisya Avni Zulvana; Sri Sumaryani (Universitas Dian Nuswantoro, 2026)
This study examines the dynamics of mother-daughter interactions in Amy Tan’s The Joy Luck Club through the lens of intergenerational cultural conflict and Brave Heart’s theory of historical trauma. This analysis investigates how mothers’ past experiences influence their relationships with their daughters in America and focuses on four mother-daughter pairs. The relationship between Suyuan Woo and Jing-mei Woo is characterized by high aspirations that Jing-mei interprets as emotional suffering due to loss and deferred dreams. Unspoken pain is transmitted through silence and emotional distance in the relationship between Ying-ying St. Clair and Lena St. Clair, which encourages passivity and a sense of powerlessness in the next generation. Meanwhile, the relationship between Lindo Jong and Waverly Jong shows how conflict arises from past trauma that emphasizes control and reputation through excessive pride and creates pressure for the daughter. As in the relationship between An-mei Hsu and Rose Hsu Jordan, the experience of loss shapes the need for assertiveness and inner strength, but this conflicts with the daughter’s values of independence. Overall, this study suggests that the tension between mother and daughter in the novel stems from inherited emotional trauma stemming from differences in cultural values between first and second-generation immigrants.